D-0-Meson R-AA in PbPb collisions at root s(NN)=5.02 TeV and elliptic flow in pPb collisions at root s(NN)=8.16 TeV with CMS - Shi, Zhaozhong; Sirunyan, A.M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
The study of charm production in heavy-ion collisions is considered an excellent probe for the properties of the hot and dense medium created in heavy-ion collisions. Measurements of D0-meson nuclear modification factor can provide strong constraints into the mechanisms of in-medium energy loss and charm flow in the medium. The measurement of D0-meson elliptic flow in pPb collisions helps us understand the strength of charm quarks coupling to significantly reduced systems which demonstrate hydrodynamic properties. In this paper, the measurements of the D0-meson nuclear modification factor in PbPb collisions at 5.02 TeV together with the new measurement of D0-meson elliptic flow in high multiplicity pPb collisions at 5.02 TeV using the two-particle correlation method will be presented.